Union catalog books of the libraries under the Department of Agriculture and the Department of Natural Resources as of Dec. 31, 1977 - Dantes, Nora V. (1978)
This is a listing by author of 5,123 books which comprise the collections of the fourteen (14) libraries under the Department of Agriculture and the Department of Natural Resources as of December 31, 1977. These materials reflect the subject specialization of these libraries, viz. agriculture, agricultural economics, fisheries and aquatic resources, forestry, lands, mining, soils, coconut, sugar and sugar technology and tobacco, as well as a number of other related fields. Each main entry includes standard bibliographic data and the location symbols representing the holding library or libraries. Each entry is preceded by an entry number. A subject index is provided.